Sacred thresholds : the door to the sanctuary in late antiquity - Opstall, Emilie Marlène van. (Religions in the Graeco-Roman World, 2018)
Sacred Thresholds. The Door to the Sanctuary in Late Antiquity offers a far-reaching account of boundaries within pagan and Christian sanctuaries: gateways in a precinct, outer doors of a temple or church, inner doors of a cella . The study of these liminal spaces within Late Antiquity - itself a key period of transition during the spread of Christianity, when cultural paradigms were redefined - demands an approach that is both interdisciplinary and diachronic. Emilie van Opstall brings together both upcoming and noted scholars of Greek and Latin literature and epigraphy, archaeology, art history, philosophy, and religion to discuss the experience of those who crossed from the worldly to the divine, both physically and symbolically. What did this passage from the profane to the sacred mean to them, on a sensory, emotive and intellectual level? Who was excluded, and who was admitted? The articles each offer a unique perspective on pagan and Christian sanctuary doors in the Late Antique Mediterranean.